Access and exclusion - Tight, Malcolm (International perspectives on higher education research ;, 2003)
International Perspectives on Higher Education Research is a series which aims to feature something of the variety of research being undertaken into higher education systems and issues outside of North America. The theme of this volume covers what is and isn't permitted, included or allowed within our higher education institutions.As with the first volume, this one deliberately sets out to convey a diversity of ideas and approaches. Thus, it includes contributions from researchers working in Australia, the Netherlands and the United Kingdom, relating to higher education experiences and systems in Australia, Europe and South Africa. They offer examples of quantitative, survey based approaches and more qualitative, interview based strategies for data collection and analysis, with methodological strategies ranging from multinational comparisons to analyses of newspaper reportage.The consideration of what it is that is being accessed or excluded from is also deliberately broad. Thus, the ten chapters in this volume do not solely concern themselves with students, and the differential access or exclusion they experience in relation to their social class, wealth, ethnicity, sex, age, religion, location, etc. They also examine access and exclusion as they impact upon academics and their managers, are experienced in terms of teaching and learning approaches, effect the content of the curriculum, relate to disciplines and what counts as academic knowledge, and are perceived externally in the media.